Impact of forest floor fire on soil carbon sequestration of Pinus roxburghii forest in Langtang National Park, Nepal - Aryal, Biva; Bhattarai, Bishnu Prasad; Pandey, Mohan; Giri, Anjana (Journal of Natural History Museum, 2018)
Forest floor fires are known to be significantly important in carbon sequestration in soil. The present study investigated the total soil carbon stock (charcoal+soil organic carbon) andCO2 flux from four different depths (0-2, 2-10, 10-30 and >30cm) in fired and unfired forest of P. roxburghii from Langtang National Park, Nepal. The aim of this study was to test the impact of forest floor fire on soil carbon sequestration. We measured total carbon stock in soil of unfired and fired sites of different intensities namely: high frequency and high intensity, high frequency and moderate intensity and high frequency and low intensity. There was significant difference (P=0.00) of the soil organic carbon between the sites and different soil depths tested by one-way ANOVA. Similarly, one-way ANOVA test showed that soil charcoal stock was significantly different (P=0.00) at different soil depths. The value of CO2 flux was increased with increasing volumetric water content and decreasing soil temperature. One-way ANOVA showed significant difference (P=0.00) of volumetric water content, soil temperature and CO2 flux between the sites. In high frequency and medium intensity site, high amount of carbon sequestrated in soil suggested that fire of medium intensity mitigates high CO2 from the atmosphere.